To protect and emit beauty - Livingston, Samuel J.; Samuels, A. Lacey (Nature chemical biology, 2021)
The plant cuticle has long been considered a barrier to volatile organic compound emission. New research reveals the paradoxical role of the cuticle as a barrier and facilitator of volatile emissions in hybrid petunia.